Contributi per una flora vascolare di Toscana. VIII (440-506) [Contributions for a vascular flora of Tuscany. VIII (440-506)] - PERUZZI, LORENZO; Daniele Viciani; Nevio Agostini; Claudia Angiolini; Nicola M. G. Ardenghi; Giovanni Astuti; Maria Rosaria Bardaro; BERTACCHI, ANDREA; Gianmaria Bonari; Sara Boni; Milan Chytrý; Fabrizio Ciampolini; et al. (2016)
Contributions for a vascular flora of Tuscany. VIII (440-506). New localities and/or confirmations concerning 67 specific and subspecific plant taxa of Tuscan vascular flora, belonging to 59 genera and 37 families are presented: Alisma (Alismataceae), Amaranthus (Amaranthaceae), Leucojum, Sternbergia, Tristagma (Amaryllidaceae), Aloe (Asphodelaceae), Erigeron, Galinsoga, Hieracium, Rhagadiolus, Silybum, Soliva, Taraxacum (Asteraceae), Impatiens (Balsaminaceae), Berberis (Berberidaceae), Cardamine (Brassicaceae), Opuntia (Cactaceae), Cephalaria, Sixalix, Succisa (Caprifoliaceae), Silene (Caryophyllaceae), Convolvulus, Ipomoea (Convolvulaceae), Aeonium (Crassulaceae), Scirpus (Cyperaceae), Equisetum (Equisetaceae), Euphorbia (Euphorbiaceae), Astragalus, Trifolium (Fabaceae), Quercus (Fagaceae), Crocus (Iridaceae), Juncus (Juncaceae), Utricularia (Lentibulariaceae), Peplis (Lythraceae), Maclura (Moraceae), Nymphaea (Nymphaeaceae), Oenothera (Onagraceae), Anacamptis, Orchis (Orchidaceae), Orobanche (Orobanchaceae), Callitriche, Veronica (Plantaginaceae), Alopecurus, Eleusine, Glyceria, Phleum (Poaceae), Persicaria, Polygonum (Polygonaceae), Groenlandia (Potamogetonaceae), Clematis, Pulsatilla, Ranunculus (Ranunculaceae), Rhamnus (Rhamnaceae), Fragaria, Potentilla, Pyracantha (Rosaceae), Galium (Rubiaceae), Sparganium (Typhaceae), Vitis (Vitaceae). In the end, the conservation status of the units and eventual protection of the cited biotopes are discussed.